THE PRINCIPAL'S LEADERSHIP AND ITS IMPACT ON TEACHER JOB SATISFACTION - Jayanti, Riska; Siraj, Arifuddin; Achruh, Andi; Rahman, Danial (Idaarah: Jurnal Manajemen Pendidikan, 2022)
This article aims to describe the principal's leadership, teacher job satisfaction, and the influence of principal's leadership on teacher job satisfaction at SMA Negeri 20 Bone. This study uses a type of field research with a quantitative approach. Respondents in this study found 30 teachers were taken as a whole with the consideration that only a few were relatively small. The instrument used in collecting data is a questionnaire distributed to research respondents. The collected data is then processed and analyzed using statistics. The results of this study indicate that: the reality of the principal's leadership at SMA Negeri 20 Bone is in the high category with a percentage of 56.7%; the reality of teacher job satisfaction at SMA Negeri 20 Bone is in the high category with a percentage of 53.3%; and principal leadership has a positive influence on teacher job satisfaction. The magnitude of the influence of the principal's leadership on teacher job satisfaction at SMA Negeri 20 Bone is 27.5%. It should be noted that the level of influence generated is quite high. Therefore, the better the visionary leadership applied by the principal, the more it contributes to teacher job satisfaction.